Correlations among the mineralogical and physical properties of halloysite nanotubes (HNTs). (2nd January 2018) - Hillier, Stephen; Brydson, Rik; Delbos, Evelyne; Fraser, Tony; Gray, Nia; Pendlowski, Helen; Phillips, Ian; Robertson, Jean; Wilson, Ian
Abstract: Twenty one samples of relatively pure tubular halloysites (HNTs) from localities in Australia, China, New Zealand, Scotland, Turkey and the USA have been investigated by X-ray diffraction (XRD), infrared spectroscopy (IR) and electron microscopy. The halloysites occur in cylindrical tubular forms with circular or elliptical cross sections and curved layers and also as prismatic tubular forms with polygonal cross sections and flat faces. Measurements of particle size indicate a range from 40 to 12, 700 nm for tube lengths and from 20 to 600 nm for diameters. Size distributions are positively skewed with mean lengths ranging from 170 to 950 nm and mean diameters from 50 to 160 nm. Cylindrical tubes are systematically smaller than prismatic ones. Features related to order/ disorder in XRD patterns e.g. as measured by a 'cylindrical/prismatic' (CP) index and IR spectra as measured by an 'OH-stretching band ratio' are related to the proportions of cylindrical vs . prismatic tubes and correlated with other physical measurements such as specific surface area and cation exchange capacity. The relationships of size to geometric form, along with evidence for the existence of the prismatic form in the hydrated state and the same 2 M 1 stacking sequence irrespective of hydration state ( i.e. 10 vs . 7 Å) or form, suggests that prismatic halloysites are the result of continued growth of cylindrical forms.